2010
DOI: 10.1371/journal.pone.0012345
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Gender-Related Changes in Contractile Properties of Non-Atrophied EDL Muscle

Abstract: BackgroundIn humans, ageing causes skeletal muscles to become atrophied, weak, and easily fatigued. In rodent studies, ageing has been associated with significant muscle atrophy and changes in the contractile properties of the muscles. However, it is not entirely clear whether these changes in contractile properties can occur before there is significant atrophy, and whether males and females are affected differently.Methods and ResultsWe investigated various contractile properties of whole isolated fast-twitch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 54 publications
8
66
5
Order By: Relevance
“…It is more likely that the use of older animals (26-28 months) in other studies than in our study (25 months) contributes to the discrepancy, as larger effects of aging on maximal muscle force are likely to be observed in the older the animal (Ballak et al 2014;Brooks and Faulkner 1988;Lynch et al 2001;McArdle et al 2004). Indeed, Chan and Head (2010) observed that even in 20-22-month-old mice, specific force was already reduced without significant muscle atrophy. Combination of the data of these studies with slightly older and younger mice than the ones used in the present study suggests that a reduction in muscle quality precedes a reduction in muscle mass.…”
Section: Discussionmentioning
confidence: 50%
“…It is more likely that the use of older animals (26-28 months) in other studies than in our study (25 months) contributes to the discrepancy, as larger effects of aging on maximal muscle force are likely to be observed in the older the animal (Ballak et al 2014;Brooks and Faulkner 1988;Lynch et al 2001;McArdle et al 2004). Indeed, Chan and Head (2010) observed that even in 20-22-month-old mice, specific force was already reduced without significant muscle atrophy. Combination of the data of these studies with slightly older and younger mice than the ones used in the present study suggests that a reduction in muscle quality precedes a reduction in muscle mass.…”
Section: Discussionmentioning
confidence: 50%
“…The changes in the contractile profiles of EDL muscles have also been observed in young and healthy mice treated with a physiological dose of statin. Statins are often prescribed to elderly patients, who are often sarcopenic and undergo a gradual change toward a slow-myofiber phenotype [54, 55]. Would these changes in contractile properties be greater in patients with chronic conditions?…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo contractility studies were performed on isolated EDLs, as previously reported 71 , 72 . Muscles were stimulated with a supra-maximal 1-ms electrical pulse and the resulting twitch recorded.…”
Section: Methodsmentioning
confidence: 99%